Caminhos da memória: na rua de significados se encontra a cozinha de pit dogs - Martins, Gabriel Sulino (2023)
The present dissertation aims to present an analysis of the sociocultural context of workers and consumers who are interlocutors related to the cuisine of “Pit Dog” on Rua 10 in Goiânia. To carry out this qualitative research, ethnography will be used as a lived experience, adapting according to the situation, to identify the variables around this relationship between subjects and cuisine, based on theories that refer to the anthropology of consumption, food and urban throughout the dissertation . The research strategy, through cyberspace and face-to-face space, due to the current context of transition between the pandemic period and an endemic one in our society. From this, this text presents the conditions for the research, experienced field factors, relationships between the researcher and the interlocutors, information obtained in the text that lead to the construction of the notion of memory, tradition, identity and street. These aspects are related to the cuisine of “Pit Dog”, such as being on Rua 10, in Goiânia, changing and adapting to the movement of the city. Thus, the main object of research, the kitchen of “Pit Dog”.